An assessment of burden of hospital-acquired pneumonia among abdominal surgical patients in tertiary university hospital in Serbia: A matched nested case-control study - Taušan, Ðorde; Rančić, Nemanja; Kostić, Zoran; Ljubenović, Nenad; Rakonjac, Bojan; Šuljagić, Vesna (Frontiers in Medicine, 2022)
Background In the population of abdominal surgical patients hospital-acquired pneumonia (HAP) significantly increases morbidity and mortality. Patients and methods Through regular hospital surveillance of patients who received abdominal operations, we identified postoperative HAP from 2007 to 2019. In an initial nested case-control study, every surgical patient with HAP was compared with three control patients without HAP. Control patients were matched to the cases by age, gender, the American Society of Anesthesiologists score, and type of surgical operation. Also, the patients with HAP, who died were compared with those who survived. Results Multivariate logistic regression analysis (MLRA) revealed that other postoperative infections, length of intensive care unit stay, use of H2RA, use of PPI/ H2RA, multiple transfusion, and use of vancomycin in surgical prophylaxis were independent RFs for occurrence of HAP. Also, MLRA identified that age, lenght of hospital stay, use of mechanical ventilation and ceftriaxone in HAP therapy were indepedenttly associated with poor outcome of HAP. All Acinetobacter baumannii isolates were resistant to aminoglycoside antimicrobial agents and showed carbapenem resistance. The most frequently used antibiotics in patients with HAP and without HAP were vancomycin and metronidazole, respectively. Conclusion Our study provided an insight into the burden of HAP in abdominal surgical patients, and highlighted several priority areas and targets for quality improvement.